A Comparative Study on English and French Simple Personal Pronoun - Beny Hamdani (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2020)
This paper critically aims to explain and describe the comparison between English and French simple personal pronoun. The comparison will be based on the form of simple personal pronoun related to the gender and show the similarities and dissimilarities between English and French simple personal pronoun. The method that is used in this study is descriptive method which covers descriptive and comparative techniques. The descriptive research is aimed to solve the problems in recent time. This study reveals some conclusion. (1) The inflection of French personal pronoun changes fully. (2) The declension of personal pronoun is complex according to gender beginning with the first person, second person and third person. Each declension of French have a specific form, depends on gender. The form of predicate is wide according to the gender. (3) The inflection of English personal pronoun is simpler than French because some terms of its declension have the same form (e.g. I, We, You, They). (4) The declension of French personal pronoun is complex and has a close relation with the predicate, because French verbs have three kinds of conjugation and its personal pronoun has its personal endings for the each term.